1999
DOI: 10.1159/000051463
|View full text |Cite
|
Sign up to set email alerts
|

What to Do when a Patient with Exocrine Pancreatic Insufficiency Does Not Respond to Pancreatic Enzyme Substitution

Abstract: In the majority of patients, pancreatin microsphere preparations containing 25,000–40,000 FIP units of lipase will lead to a clinical improvement and reduction of steatorrhea in patients with exocrine pancreatic insufficiency. In patients failing to respond, the following stepwise procedure is recommended: increasing enzyme dosage; checking the patient’s compliance; reevaluating the diagnosis; and as a last resort to decrease fat intake or adding H2-blockers or proton pump inhibitors. Although this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 38 publications
0
4
0
2
Order By: Relevance
“…19 Reasons that steatorrhea persists in CP patients include patient compliance factors, incorrect diagnosis due to lack of identification of other possible etiologies (ie, bacterial overgrowth), inadequate doses of enzymes, decreased bioavailability (destroyed by acid environment), asynchrony of gastric empty rate of food and pancreatic enzymes. 2,12,21 Optimizing enzyme therapy is the primary treatment for fat malabsorption.…”
Section: Pancreatic Enzyme Therapy Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Reasons that steatorrhea persists in CP patients include patient compliance factors, incorrect diagnosis due to lack of identification of other possible etiologies (ie, bacterial overgrowth), inadequate doses of enzymes, decreased bioavailability (destroyed by acid environment), asynchrony of gastric empty rate of food and pancreatic enzymes. 2,12,21 Optimizing enzyme therapy is the primary treatment for fat malabsorption.…”
Section: Pancreatic Enzyme Therapy Challengesmentioning
confidence: 99%
“…2 Dosing varies; Lankisch 21 recommends microcapsulated, enteric-coated (1.4 mm, pH 5.5) taken with meals 25 000-40 000 units/meal to start and increase dose to 2 to 3 times the initial dose, if steatorrhea persists. 21 4. Educate about medications: Depending on the prescription some patients have a high pill burden that can decrease success due to noncompliance.…”
Section: Pancreatic Enzyme Therapy Challengesmentioning
confidence: 99%
“…55,102 In compliant patients not responding to PES, increasing the dose of PES by 2-3 fold along with distribution of calories across 5-6 smaller meals is …”
Section: Treatment Failures Patient Compliance and Alternativesmentioning
confidence: 99%
“…It has been shown that the use of gelatin capsules of pancreatic microsphere containing supplements, containing 25,000 to 40,000 units of lipase will lead to a significant reduction of steatorrhea in patients with CP. 36 In those patients who fail pancreatic enzyme therapy, a gastric acid suppressing agent, such as a proton pump inhibitor, should be added to inhibit gastric acid degradation of orally ingested pancreatic enzymes.…”
Section: Nutrition Support Modalitiesmentioning
confidence: 99%